Responsible CSR Communications: Avoid “Washing” Your Corporate Social Responsibility (CSR) Reports and Messages - Bernardino, Paula (Journal of Leadership, Accountability and Ethics, 2021)
With the rise of Corporate Social Responsibility (CSR) reporting, questions have emerged regarding its true utility; CSR reports may more closely resemble marketing materials than financial statements as much of the data companies provide can be cherry picked. For example in 2011, only 20% of S&P 500 companies published CSR reports vs 85% in 2017 and 90% in 2019. Why is this relevant for communicators? Because the responsibility of producing and promoting CSR reports very often falls under the responsibility of the corporate communications team. How to avoid "CSR-washing" and all the other “washing” incidents – green-washing, blue-washing, rainbow-washing, vegan-washing,...? How to focus on portraying the organization as a truly and authentic dedicated corporate citizen? In-depth interviews with 15 senior communication practitioners in Canada helped identify what are “authentic” and “responsible” communications in the CSR space: using facts and testimonials, being transparent, showing authenticity as well as demonstrate the clear alignment with the organization’s purpose.